2022
DOI: 10.1029/2021jb022574
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Imaging of Crust Beneath the Western Tibet‐Pamir and Western Himalaya Using Ambient Noise and Earthquake Data

Abstract: The Himalaya-Tibet-Pamir mountain belts (Figure 1) have an evolutionary history beginning about 60 Myr ago with the closure of the Tethys Ocean followed by the collision of the Eurasian and Indian landmass (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 204 publications
(544 reference statements)
0
5
0
Order By: Relevance
“…Previous studies have proved that the underthrusting Indian lower crust reaches varying latitudes below the southern LT, and undergoes partial eclogitization or underplating by mantle mafic materials (Kumar et al., 2022; Shi et al., 2016; Q. Xu et al., 2017). Three NE‐trending PRFs sections crossing the EHS and surrounding area have revealed that the underthrusting Indian lower crust extends beyond at least the Jiali fault (C. Y. Wang et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have proved that the underthrusting Indian lower crust reaches varying latitudes below the southern LT, and undergoes partial eclogitization or underplating by mantle mafic materials (Kumar et al., 2022; Shi et al., 2016; Q. Xu et al., 2017). Three NE‐trending PRFs sections crossing the EHS and surrounding area have revealed that the underthrusting Indian lower crust extends beyond at least the Jiali fault (C. Y. Wang et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, thermodynamic numerical predictions demonstrate that the 3‐D geometry of a curved subduction slab is important for producing the observed deformation patterns and exhumation at syntaxes (Bendick & Ehlers, 2014). Tomographic images reveal that the subducting Indian plate reaches the Bangong‐Nujiang suture at depths of 100–150 km (Dubey et al., 2022), but the underthrusting of the Indian lower crust, which is widely reported in the Himalayan orogenic belt (Kumar et al., 2022), is rarely observed in the core of the EHS.…”
Section: Introductionmentioning
confidence: 99%
“…The single-day data is then subjected to time-domain normalization (running absolute mean) and spectral whitening, followed by computing the geometrically normalized cross-correlations (CCGN; Schimmel et al 2011) for all possible raypaths. The daily cross-correlations are further stacked using the time-frequency phaseweighted stack (tf-pws) approach (Schimmel et al 2011) to enhance the signal-to-noise ratio (e.g., Acevedo et al 2019;Kumar et al 2022). We combine the causal and anti-causal parts of the daily cross-correlation and produce symmetric stacked correlations.…”
Section: Group Velocity Dispersion Measurements and Noise Source Char...mentioning
confidence: 99%
“…Broader low-velocity zone at mid-crustal depth beneath the southern parts of Tibet and Karakoram fault is due to the presence of partial melting and/or aqueous fluids. Kumar V., et al (2022) used ambient noise cross-correlations from 530 seismological stations along with surface wave observations from 1,261 earthquakes to image the crust beneath the western Himalaya-Asia convergence zone encompassing western Himalaya-western Tibet-Ladakh-Karakoram-Pamir-Hindu Kush. The seismological data from the PASSCAL experiments, the Global Seismograph Network, experiments in Kyrgyzstan, Kazakhstan, Tajikistan, China, Nepal and western Tibet, French deployments in western Kunlun and Kazakhstan and Indian deployments in the western Himalaya were used in this study that resulted in 22,726 inter-station Rayleigh wave dispersion measurements in the period band of 5 to 60 s at a horizontal resolution of less than 0.5 • ×0.5 • .…”
Section: Himalayamentioning
confidence: 99%